Celah Regulasi Penegakan Hukum dalam Mengatasi Pencucian Uang dari Kejahatan Ekonomi melalui Aset Digital di Indonesia - Iman Nurjaman (Jurnal Hukum Lex Generalis, 2025)
Digital assets such as cryptocurrency and NFTs are growing rapidly in Indonesia and have become an important part of the digital financial ecosystem. However, this technology is also being exploited in money laundering practices due to its anonymous, cross-border nature and lack of comprehensive legal regulation. This study aims to examine regulatory gaps in law enforcement efforts to combat money laundering from economic crimes through digital assets. The methodology employed is a normative legal approach, utilizing conceptual analysis and doctrinal analysis of relevant legislation. The findings reveal that existing regulations remain general in nature and have not addressed technical aspects such as the seizure of digital assets, smart contracts, and DeFi platforms. In addition, overlapping authority between institutions, weak real-time supervision, and the lack of digital forensic capacity of law enforcement agencies exacerbate the gaps in law enforcement. Therefore, legal reform is needed through specific digital asset legislation, institutional capacity building, and the strengthening of adaptive surveillance technology to address the dynamics of digital crime.